Jasmonic acid and salicylic acid induce the accumulation of sucrose and increase resistance to chilling injury in peach fruit. (25th February 2021) - Zhao, Yaoyao; Song, Congcong; Qi, Shuning; Lin, Qiong; Duan, Yuquan
Abstract: BACKGROUND: Salicylic acid (SA) and jasmonic acid (JA) can both enhance resistance of chilling injury (CI) in cold‐storage peach fruit, but the regulatory mechanisms involved and whether there is a coordinated regulation between them is unclear. In this study, postharvest peach fruit were treated with an aqueous SA solution for 15 min or an aqueous JA solution for 30 s before storage at 4 °C for 35 days. RESULTS: SA and JA treatments both delayed and reduced development of internal browning (a symptom of CI) and induced the accumulation of hydrogen peroxide and sucrose. The SA and JA also reduced catalase and peroxidase activities, which are involved in hydrogen peroxide generation. The SA and JA treatments significantly regulated the transcript abundance of genes related to sucrose biosynthesis and degradation consistent with the observed increase in sucrose content. CONCLUSION: These results intimate that JA and SA may be involved in coordinating the alleviation of CI via increased accumulation of sucrose. © 2021 Society of Chemical Industry